Narration and Self-Identity in Paul Ricoeur (Damascus University Journal of arts and humanities sciences, 2022)
The research deals with Paul Ricoeur's hermeneutic philosophy of the concept of narration and its connection to life, time and self-identity, in that self engaged in practice and action, whose personal and even collective life can only be accessed in the narrative anecodotal plot of an entire life of a speaker and active self and what it narrates ultimately constitutes her narrative identity presented by Paul Ricoeur as a solution to a fixed 'sameness' identity that doesn't accept change and a 'self' identity that changes and remains self-preserving.
Keywords: Hermeneutic; self; sameness